Status of ICT Application in Agriculture –an Overview - N.K.Khare, Sonam Agrawal, Parvez Rajan, (Indian Journal of Extension Education, 2022)
Information and communication is very important in agriculture. Ever since people have grown crops, raised livestock, and caught fish, they have sought information from one another. Where can I buy the improved seed or feed this year? Who is paying the highest price at the market? How can I participate in the government’s credit program? Producers rarely find it easy to obtain answers to such questions, Updated information allows the farmers to cope with and even benefit from these changes. Providing such knowledge can be challenging, however, because the highly localized nature of agriculture means that information must be tailored specifically to distinct conditions. In which ICT can play a major role, that’s why in this paper mainly focus on the different ICT project like Fisher Friend project, Fisher Friend project, Helpline hello Uttam, Expert system, Kisan Call Center, ICT based Kisan Mobile Sandesh, e – choupal, MSSRF, Agrisnet , e- arik , etc which help to farmer to get right information at right time. The continued increase in globalization and integration of food markets has intensified competition and efficacy in the agriculture sector, and has brought unique opportunities to include more smallholders into supply chains. Yet in the same vein, agriculture faces a range of modern and serious challenges, particularly in developing countries different ICT project help to cope up the problems.